2013
DOI: 10.1186/1471-2180-13-176
|View full text |Cite
|
Sign up to set email alerts
|

An easy, simple inexpensive test for the specific detection of Pectobacterium carotovorum subsp. carotovorum based on sequence analysis of the pmrA gene

Abstract: BackgroundThe species Pectobacterium carotovorum includes a diverse subspecies of bacteria that cause disease on a wide variety of plants. In Morocco, approximately 95% of the P. carotovorum isolates from potato plants with tuber soft rot are P. carotovorum subsp. carotovorum. However, identification of this pathogen is not always related to visual disease symptoms. This is especially true when different pathogen cause similar diseases on potato, citing as an example, P. carotovorum, P. atrosepticum and P. was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 31 publications
2
13
0
1
Order By: Relevance
“…Whereas the isolates showed the ability to hydrolyze β-glucosidase, gelatins and citrates, inositol and D-sorbitol assimilation tests were negative, although bacterial strains had the ability to use Dglucose, L-arabinose, D-mannitol, D-sucrose, D-melibiose, amygdalin, and L-rhamnose. Similar results are presented in the works of Terta et al [32], Kettani-Halabi et al [33] and are considered as diagnostic biochemical signs.…”
Section: Discussionsupporting
confidence: 89%
“…Whereas the isolates showed the ability to hydrolyze β-glucosidase, gelatins and citrates, inositol and D-sorbitol assimilation tests were negative, although bacterial strains had the ability to use Dglucose, L-arabinose, D-mannitol, D-sucrose, D-melibiose, amygdalin, and L-rhamnose. Similar results are presented in the works of Terta et al [32], Kettani-Halabi et al [33] and are considered as diagnostic biochemical signs.…”
Section: Discussionsupporting
confidence: 89%
“…The Pcc Jo-isolates were strongly differentiated from other Pectobacterium responsible for disease in potato including Pca. Kettani-Halabi et al (2013) indicated that pmrA sequence analysis was a reliable tool for detection and identification of Pcc and to determine genetic diversity. The Pcc Jo-isolates from different regions did not cluster according to locations and this could be attributed to the fact that potato seeds in Jordan are mainly from one source.…”
Section: Discussionmentioning
confidence: 99%
“…The isolates were subjected to PCR amplification using pmrA primer set: F0145: TACCCTGCAGATGAAATTATTGATT-GTTGAAGA; E2477: TACCAAGCTTTGGTTGTTCCCCTTTGGTCA (Kettani-Halabi et al, 2013). Primers were designed based on the sequence of pmrA gene in Erwinia species.…”
Section: Characterization Of Isolates With Pmra Markermentioning
confidence: 99%
See 1 more Smart Citation
“…Plant pathogens have been a threat to crops and pose a danger to food security. Potato blackleg, which is caused by various soft rot coliforms such as Pectobacterium ( 1 ), is one of the major concerns worldwide. Plant pathogenic characteristics, such as production of virulence factors, can be regulated from their communication, which is also known as quorum sensing (QS) ( 2 , 3 ).…”
Section: Genome Announcementmentioning
confidence: 99%